THE STRATEGY OF TRANSLATING PUN IN ENGLISHINDONESIAN SUBTITLE OF AUSTIN POWERS: GOLDMEMBER - Ari Natarina (Soegijapranata Catholic University, 2012)
This paper concerns about the translation of pun in comedy movie's subtitle. The data is taken from a comedy movie Austin Powers: Goldmember. There are three problems that are being discussed in this paper. The first problem is the effect of different types of pun to translatability. Second, the strategies in translating different types of pun are discussed The last is the assessment of translation using register analysis in evaluating the extent of loss and gain occurred in the translation process. Key words: pun, translatability, translation strategy, register theory